2018
DOI: 10.1002/hep.30076
|View full text |Cite
|
Sign up to set email alerts
|

Ad Libitum Mediterranean and Low‐Fat Diets Both Significantly Reduce Hepatic Steatosis: A Randomized Controlled Trial

Abstract: Although diet-induced weight loss is first-line treatment for patients with nonalcoholic fatty liver disease (NAFLD), long-term maintenance is difficult. The optimal diet for improvement in either NAFLD or associated cardiometabolic risk factors, regardless of weight loss, is unknown. We examined the effect of two ad libitum isocaloric diets (Mediterranean [MD] or low fat [LF]) on hepatic steatosis (HS) and cardiometabolic risk factors. Subjects with NAFLD were randomized to a 12-week blinded dietary intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
212
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 155 publications
(220 citation statements)
references
References 43 publications
7
212
1
Order By: Relevance
“…No significant differences were observed between, or within groups, in markers of insulin resistance, and measures of both arterial stiffness and liver stiffness (as assessed by FibroScan). (10) Collectively, although some of the observed benefits on liver fat content may have been attributed to a small decrease in abdominal adiposity (visceral fat mass) and an increase in physical activity energy expenditure, we consider that these findings are clinically relevant for patients with NAFLD and provide support for the view that both MD and LFD have the potential to improve HS (by approximately −25% to −30%), even in the absence of significant weight reduction. (10) There are some differences in the benefits conferred by the MD versus the LFD on cardiometabolic risk factors, as illustrated in the linked article.…”
Section: See Article On Page 1741mentioning
confidence: 60%
See 4 more Smart Citations
“…No significant differences were observed between, or within groups, in markers of insulin resistance, and measures of both arterial stiffness and liver stiffness (as assessed by FibroScan). (10) Collectively, although some of the observed benefits on liver fat content may have been attributed to a small decrease in abdominal adiposity (visceral fat mass) and an increase in physical activity energy expenditure, we consider that these findings are clinically relevant for patients with NAFLD and provide support for the view that both MD and LFD have the potential to improve HS (by approximately −25% to −30%), even in the absence of significant weight reduction. (10) There are some differences in the benefits conferred by the MD versus the LFD on cardiometabolic risk factors, as illustrated in the linked article.…”
Section: See Article On Page 1741mentioning
confidence: 60%
“…Notably, diet adherence was higher with the MD than with the LFD (88% vs. 64%); and among the secondary outcomes, the researchers found that the Framingham Risk Score, plasma lipids, and hemoglobin A1c improved significantly from baseline in the MD group only. No significant differences were observed between, or within groups, in markers of insulin resistance, and measures of both arterial stiffness and liver stiffness (as assessed by FibroScan) …”
mentioning
confidence: 65%
See 3 more Smart Citations